Constructing and Disseminating Urban Cultural Tourism Media Image through Short Videos - Zhang, Fuyu (Transactions on Social Science, Education and Humanities Research, 2024)
With the widespread adoption of mobile internet and the rise of short video platforms, the modes of information dissemination are undergoing profound changes. As an emerging content format, short videos, characterized by their intuitiveness, vividness, and fragmented nature, have rapidly occupied a significant amount of user time. This is particularly true for the construction and dissemination of urban cultural tourism media images, where short videos have become an indispensable tool. Urban cultural tourism media images refer to the representation of a city’s culture and tourism through various media means, playing a crucial role in the city’s development and reputation. However, traditional methods of disseminating cultural tourism images have evident shortcomings. With the emergence of short videos, new opportunities have arisen for the construction and dissemination of urban cultural tourism media images. The relatively low production threshold of short videos allows cities to showcase their cultural and tourism resources through various creative means, attracting more visitors and gradually enhancing the city’s competitiveness and local economic development.